Information Communication Technology and Terrorism in Nigeria: Digitalization for Enhanced National Security - Latifat Adeola Odeniyi; Haruna Ishola Abdullahi (International Journal of Information Systems and Informatics, 2022)
Terrorism is a global issue, it leads loss of lives and property. Nigeria is one of the countries that are groaning under terrorist attacks. Terrorism as an organized crime has claimed more than one million lives, property worth billions of Naira have been destroyed. Hence, this paper assesses Information Communication Technology (ICT) and terrorism in Nigeria for enhanced national security. The study adopts qualitative research methods, data were sourced secondarily through the content analysis of edited textbooks, peer- reviewed journals, and credible online resources. The study anchors on routine activity and modernization theories. Findings showed that there are lapses in the current security architecture in Nigeria; there is a lack of coordination among the existing security structures which are inadequate and archaic. The study recommends the effective application of Information Communication Technology (ICT) to checkmate terrorism. The study will be beneficial to entire citizens, government at various levels, ministries of defense, Non-governmental organizations and researchers in the field of Security and Criminology.